HEDONISM REFLECTED ON CELEBRITIES INSTAGRAM (CELEBGRAM) ACCOUNT - Pasha, Nariza Ayu; Gumay, Khalifah Fathonia (Universitas Muhammadiyah Surakarta, 2023)
This study aims to investigate the indicators of hedonism and the most dominant hedonistic orientation reflected on celebrities' accounts. This study uses the accounts of four well-known Indonesian celebrities as research samples. The results of this study were analyzed using the semiotic theory of Roland Barthes. The results showed that there were eleven hedonism indicators reflected by celebrities on their Instagram accounts, namely self-expression, hobby, addictive substance, physical beauty, fashionable appearance, education, achievement, work, social activity, relationship, comedy and religiosity. From these indicators, it is known that universal hedonism and egoistic hedonism are the most dominant hedonistic orientations on celebrities' accounts.